Apolipoprotein A1 is associated with pulmonary vascular resistance and adverse clinical outcomes in patients with pulmonary hypertension secondary to heart failure. (27th July 2022) - Yu, Wande; Dujiang, Xie; Yi, Wang; Guanwen, Ding; Mengyu, Zhang; Chang, Pan; Aikai, Zhang; Juan, Zhang; Linlin, Zhu; Hang, Zhang
Abstract: Pulmonary hypertension secondary to heart failure (HF‐PH) combined with pulmonary vascular remodeling has a high mortality rate. Apolipoprotein A1 (ApoA1) has been shown to adversely affect outcomes in patients with HF. A prospective follow‐up study was performed on 239 consecutive patients with HF‐PH who underwent right heart catheterization. Proteomics technology was used to analyze different proteins in plasma between post‐ and precapillary pulmonary hypertension (CpcPH) and isolated postcapillary pulmonary hypertension (IpcPH) filtered by propensity score matching. Ultimately, 175 patients were enrolled and followed for an average of 4.4 years. Lipoprotein components in plasma were measured, and the following clinical events were tracked. Proteomics data showed that lipid metabolism and inflammation were different between CpcPH and IpcPH. ApoA1 levels in HF‐PH patients with CpcPH were lower than those in HF‐PH patients with IpcPH. The patients with lower ApoA1 levels (≤1.025 g/L) were in a higher New York Heart Association class and had high levels of NT‐proBNP, mean pulmonary artery pressure, PVR, and diastolic pressure gradient. Besides, HF‐PH patients with lower ApoA1 levels had a 2.836‐fold higher relative risk of comorbid CpcPH compared with patients with higher ApoA1 levels. Moreover, patients with lower ApoA1 levels had a lower survival rate after adjusting for CpcPH. In conclusion, ApoA1 levels were negatively correlated with PVR levels. Lower ApoA1 levels were an independent risk factor for pulmonary vascular remodeling in HF‐PH patients. The survival of HF‐PH patients with lower ApoA1 levels was reduced.